Sistema de interpretación de suelos agrícolas en el laboratorio de suelos de la UNSM-T. - García Hidalgo, Carlos Gustavo (2015)
The present research, interpretation system of agricultural soils in the soils laboratory UNSM-T; general objective, develop a system of information that interprets the results of a soil analysis at the Laboratory of Soil UNSM -T; likewise specific objectives, perform a simple interpretation that facilitates proper land use of farmers in the San Martin region, recommend the application of certain technical actions to achieve better results in the fields of producers, complement the service provided by the Soil Laboratory of the UNSM -T. For its development methodologies were used. For the collection of information, surveys, interviews, as well as review and assessment documents were made; Software development methodology RUP and Knowledge Engineering John Durkin under development approach was used expert systems and their implementation is done with the ASP language and IIS Server on Windows platform. Seen the need to improve the process of interpretation of soil analysis in the laboratory of soils UNSMT and taking aim at improving the performances mentioned above and support to the laboratory if they provide to beneficiaries in the region San Martin ( students, postgraduate students agrochemical companies and farmers will have an easier interpretation and therefore a good fertilizing his field resulting in a significant improvement in the level of production in tons per year; this thesis aims to support and optimize through Information system of knowledge the process of interpretation of a soil analysis laboratory UNSM-T.